The Impact of Employee Training, Job Satisfaction, and Organizational Commitment on Employee Performance in the Tech Industry - Siswanto, Agus (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
In the contemporary landscape of the tech industry, the quest for enhanced employee performance stands as a cornerstone for organizational success and competitive advantage. This pursuit necessitates a comprehensive understanding of the intricate interplay between various factors influencing employee performance. The primary objective of this research is to empirically investigate the impact of employee training, job satisfaction, and organizational commitment on employee performance within the tech industry. This study adopts a qualitative research design, specifically a literature review approach, to comprehensively explore the impact of employee training, job satisfaction, and organizational commitment on employee performance in the tech industry. In conclusion, the study elucidates the significant impact of employee training, job satisfaction, and organizational commitment on employee performance within the tech industry. The comprehensive review of existing literature demonstrates that targeted and continuous employee training programs are essential for enhancing the skills and knowledge necessary for optimal job performance.